Effect of III/V ratio on the polarity of AlN and GaN layers grown in the metal rich growth regime on Si(111) by plasma assisted molecular beam epitaxy. (19th May 2015) - Agrawal, Manvi; Radhakrishnan, K.; Dharmarasu, Nethaji; Pramana, Stevin Snellius
Abstract: Wet chemical etching, reflection high energy electron diffraction, scanning electron microscope and convergent beam electron diffraction have been employed to study the polarities of AlN and the subsequently grown GaN as a function of metal flux in the metal rich growth regime. Both AlN and GaN exhibited metal polarity in the intermediate growth conditions. However, in the droplet growth regime, the polarity of AlN and GaN were N polar and Ga polar, respectively. It was observed that Ga polar GaN could be obtained on both Al and N polar AlN. AlGaN/GaN high electron mobility transistor (HEMT) heterostructure exhibiting hall mobility of 900 cm 2 V −1 s −1 and sheet carrier density of 1.2 × 10 13 cm −2 was demonstrated using N polar AlN which confirmed Ga polarity of GaN. Al metal flux was likely to play an important role in controlling the polarity of AlN and determining the polarity of the subsequent GaN grown on Si(111) by plasma assisted molecular beam epitaxy (PA-MBE).